Penyuluhan Kesehatan tentang Pencegahan Penyakit Asam Urat di Desa Tanjung Serang Tahun 2026 - Irdan Irdan; Sanjaya Sanjaya; Rahmanda Pranata; Tria Seprina; Putri Handayani; Yelika Tiara Putri Sijabat; Rofif Frari Aggrahi; Chelcia Lumban Toruan; Yunita Yunita; Wanda Miliya Apriliani; Liza Anggraini; Amel Nur Zahara; Bias Sandy Permadi; Taufik Zikki Mar Bun Bun HSB (JURNAL PENGABDIAN KADER BANGSA, 2026)
Gout is one of the non-communicable diseases whose prevalence has increased due to changes in lifestyle and the consumption of foods high in purines. Limited public knowledge can influence efforts to prevent and control this disease. This community service activity aimed to describe the implementation of health education on gout prevention in Tanjung Serang Village in 2026. The method used referred to an action research approach consisting of observation, village community deliberation, implementation of health education, and descriptive evaluation. The educational materials were delivered through lectures, interactive discussions, and educational media covering risk factors, signs and symptoms, as well as preventive measures through a low-purine diet and a healthy lifestyle. The results showed active community participation involving 104 respondents in the health education activity. Participants were able to identify risk factors, types of high-purine foods, and preventive measures for gout through healthy dietary habits and physical activity. In addition, health screening activities such as uric acid and blood pressure checks helped the community better understand their health conditions.